The Knowledge lab on climate-resilient food systems - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
Food systems fundamentally influence the environment of the planet, the livelihoods of billions of people (including most of the world’s poor), and the nutrition of every human being. Robust food systems can serve as catalysts for achieving the Sustainable Development Goals, but their current weaknesses are a major source of vulnerability to a variable and changing climate. IFPRI’s Knowledge Lab on Climate-Resilient Food Systems will identify and deploy innovative approaches to achieving resilient food systems in a context of climate change. The Knowledge Lab, an integral element of IFPRI’s strategic focus on fostering a sustainable food supply, rests on three operational pillars: building expertise, collaborative research, and partnerships for impact.